Plant-Based Air Purification with Real-Time Monitoring: A Hybrid Hydroponic Sensor System for IAQ Enhancement - Wong, Scanly; Mad Sahar, Nan (Evolution in Electrical and Electronic Engineering, 2025)
This study addresses the growing concern of poor indoor air quality (IAQ) in urban environments, which has been associated with various health problems. Many conventional air purification systems are energy-intensive and less effective against certain gaseous pollutants. To overcome these challenges, a hybrid hydroponic-sensor system is developed, combining air purification by plants with IoT-enabled real-time environmental monitoring. Spider plants, golden pothos, and philodendron gold, known for their natural air-cleaning capabilities, were cultivated using a nutrient film technique (NFT) setup. Environmental parameters including temperature, humidity, CO₂, total volatile organic compounds (TVOCs), and pH were monitored using an ESP32 microcontroller integrated with SHT31, CJMCU-811, and analog pH sensors. Data was displayed on an LCD and accessible via the Blynk mobile application. A three-week experimental evaluation demonstrated a reduction of 20–30% in CO₂ and 35–50% in TVOC concentrations, while maintaining optimal plant growth conditions. This affordable and low-power consumption solution enhances IAQ and contributes to healthier indoor environments in homes, offices, and classrooms. The findings highlight the potential of integrating plant-based phytoremediation with off-the-shelf IoT technology for sustainable and scalable indoor air management.